2017
DOI: 10.3791/56228
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase Activity Assay Using Near-infrared Fluorescent Labeled DNA Visualized by Acrylamide Gel Electrophoresis

Abstract: For any enzyme, robust, quantitative methods are required for characterization of both native and engineered enzymes. For DNA polymerases, DNA synthesis can be characterized using an in vitro DNA synthesis assay followed by polyacrylamide gel electrophoresis. The goal of this assay is to quantify synthesis of both natural DNA and modified DNA (M-DNA). These approaches are particularly useful for resolving oligonucleotides with single nucleotide resolution, enabling observation of individual steps during enzyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In this study, extracted total RNA was verified by gel electrophoresis, quantitative nucleic acid detection and PCR analysis. As a routine examination method [ 24 32 ], all samples were tested by 1.0% of modified agarose gel electrophoresis. From Fig 1A , 28 s and 18 s and 5 s stripes were clear with high brightness and no obvious towing degradation phenomenon, which suggested that this modified method from CHAN assured RNA integrity.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, extracted total RNA was verified by gel electrophoresis, quantitative nucleic acid detection and PCR analysis. As a routine examination method [ 24 32 ], all samples were tested by 1.0% of modified agarose gel electrophoresis. From Fig 1A , 28 s and 18 s and 5 s stripes were clear with high brightness and no obvious towing degradation phenomenon, which suggested that this modified method from CHAN assured RNA integrity.…”
Section: Resultsmentioning
confidence: 99%